Understanding the caregiver experience: a cross-sectional study of caregiver burden among those caring for chronically ill children in Jordan - Lina Alshadfan; Mohammad Deameh; Aya Alhyary; Mohammad Da’meh; Khaled El-Areidi; Mahmod Sharqi; Ahmad Alkayed; Khaled Da’meh; Osama Alhaj Ali; Ghada Alkhdour; Rahaf Abu-Shai’rah; Basel Akash; et al. (BMJ Paediatrics Open, 2025)
Background Caregivers of children with chronic illnesses often experience varying levels of burden, influenced by multiple psychosocial and environmental factors. Understanding the specific sources and determinants of caregiver burden is crucial for developing supportive interventions, particularly in regions where research remains limited.Methods A cross-sectional study was conducted among 352 caregivers to assess the extent and nature of caregiving burden. Burden levels were measured using a validated Arabic version of the Zarit Burden Interview (ZBI-A) questionnaire, and associations with sociodemographic factors were examined.Results The study included 352 caregivers of children with chronic illnesses, with a mean child age of 9.5 years (SD=4.4) and a majority being boys (64.5%). The mean age of the caregivers was 40.3 years (SD=9.2, range: 20–70 years), with most being mothers (83.8%). According to the ZBI-A Score, 38.6% experienced no-to-mild burden, 40.6% reported mild-to-moderate burden and 20.8% faced high burden. The most prominent burden sources were feelings of inadequacy, stress balancing childcare with other responsibilities and insufficient time for self-care (mean: 2.83, 2.61 and 2.47, respectively). Moderate burdens included fatigue, lack of privacy and health deterioration (mean: 2.07, 2.07 and 2.00, respectively), while the lowest level was observed for anger (mean: 1.74). Lower family income and non-attendance of children in school were significantly associated with higher caregiver burden (p=0.04 and 0.02, respectively).Conclusion Caregiver burden is a significant issue among parents of chronically ill children, shaped by emotional, social and financial stressors. Strengthening school-based support services and addressing financial hardships may substantially reduce caregiver burden and improve family well-being.